EduCan trial: study protocol for a randomised controlled trial on the effectiveness of pain neuroscience education after breast cancer surgery on pain, physical, emotional and work-related functioning. Issue 1 (4th January 2019) - De Groef, An; Devoogdt, Nele; Van der Gucht, Elien; Dams, Lore; Bernar, Koen; Godderis, Lode; Morlion, Bart; Moloney, Niamh; Smeets, Ann; Van Wilgen, Paul; Meeus, Mira
Abstract : Introduction: Over the past decades, awareness on the importance of educational interventions in cancer pain management has increased. However, education is often restricted to biomedical pain management instructions. A more modern educational approach, also known as pain neuroscience education (PNE), explains pain from a biopsychosocial perspective. We hypothesise that this more comprehensive educational approach in the early treatment phase of breast cancer will lead to more beneficial effects for cancer pain management. Therefore, the aim of the present study is to investigate the effectiveness of this PNE intervention, in addition to best evidence physical therapy modalities for treatment and prevention of pain, physical, emotional and work-related functioning after breast cancer surgery, compared with a traditional biomedical educational intervention. Methods: A double-blinded randomised controlled trial has been started in November 2017 at the University Hospitals of Leuven. Immediately after breast cancer surgery, all participants (n=184) receive a 12-week intensive standard physical therapy programme. They receive three additional refresher sessions at 6, 8 and 12 months postsurgery. In addition, participants receive three educational sessions during the first-month postsurgery and three 'booster sessions' at 6, 8 and 12 months postsurgery. In the intervention group, the content of the education sessions is based on the modern PNE approach. Whereas in the control group, the education is based on the traditional biomedical approach. The primary outcome parameter is pain-related disability 1 year after surgery. Secondary outcomes related to other dimensions of pain, physical, emotional and work-related functioning at 1-week, 4, 6, 8, 12 and 18 months postsurgery. Ethics and dissemination: The study will be conducted in accordance with the Declaration of Helsinki. This protocol has been approved by the ethical committee of the University Hospitals of Leuven. Results will be disseminated via peer-reviewed scientific journals and presentations at congresses. Trial registration number: NCT03351075 .